Potato yield reduction by artificial defoliation at four different ages - Butignol, Cesar Assis; Reis, Maurício Sedrez dos (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment in Palhoça, SC, Brazil (27°36'S), was carried out to determine the effect of 50% and 100% of leaf blade cut on potato plants (Solanum tuberosum L.), cv. Achat, with 15, 30, 45 and 60 days of age, after a 75% of emergence of certificated tuber seeds. The trial was conducted as a 3 x 4 factorial in completely randomized blocks with four repetitions. The statistical analysis through the F test showed that new leaves were emerged at 15 and 30 days of age. The tuber yield decreased as a consequence of the defoliation at 30 and 45 days of age. Tuber number did not show modification after the treatments. It was concluded that the level of damage in yield presented in the plants was affected by the age and defoliation levels. The tuber sensibility to age and defoliation was greater at 30 and 45 days than at 15 and 60 days of age.